An antibacterial CF / PEEK composite material and its preparation method and application
By combining plasma treatment and Ag+ on the CF/PEEK composite material, combined with electrostatic powder spraying and hot pressing processes, the existing antibacterial modification methods are solved, and the good antibacterial properties of the CF/PEEK composite material are achieved.
Patent Information
- Application Number
- CN202411194816.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-08-29
AI Technical Summary
The existing antibacterial modification methods for CF/PEEK composites are unsafe to operate and are difficult to control.
Functional groups were introduced by plasma treatment of the polyether ether ketone powder, combined with Ag+, and the antibacterial PEEK powder was sprayed onto the surface of the carbon fiber cloth by electrostatic powder spraying. After heat treatment and ultraviolet irradiation, CF/PEEK composite material with good antibacterial properties was prepared.
This method is safe and controllable in operation, and can effectively improve the antibacterial properties of CF/PEEK composite materials, reduce silver shedding, and improve the long-term antibacterial effect of the material.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of orthopedic internal fixation materials, and in particular to an antibacterial CF / PEEK composite material and a preparation method and application thereof. Background Art
[0002] CF / PEEK (carbon fiber / polyetheretherketone) composite materials have become a new generation of orthopedic internal fixation materials due to their high strength, light weight, elastic modulus close to that of bones, no artifacts in radiological examinations, and no impact on radiological treatment. At present, some institutions have completed the development of CF / PEEK composite materials for bone implant medical devices, such as bone plates. The infection problem in orthopedic implant surgery has always been a difficult problem that plagues clinical practice. Unlike mature materials such as titanium alloys, which have more research on antibacterial technology, there are fewer studies on antibacterial modification of CF / PEEK composite materials, such as orthopedic implant materials.
[0003] At present, the common method for antibacterial modification of CF / PEEK composites is to sulfonate PEEK with concentrated sulfuric acid, and then use the sulfonic acid group to load the antibacterial material (such as the use of sulfonic acid groups to load graphene oxide-hydroxyapatite composites in patent CN202110302272.7). This method requires the use of concentrated sulfuric acid for sulfonation, which has operational safety issues and is difficult to control the sulfonation process. Summary of the invention
[0004] In order to solve the technical problems that the existing antibacterial modification methods of CF / PEEK composite materials are unsafe to operate and difficult to control, the present invention provides a method for preparing an antibacterial CF / PEEK composite material. The preparation method is relatively safe and controllable, and can make the prepared antibacterial CF / PEEK composite material have good antibacterial properties.
[0005] The specific technical scheme of the present invention is:
[0006] In a first aspect, the present invention provides a method for preparing an antibacterial CF / PEEK composite material, comprising the following steps:
[0007] (1) Plasma treatment of polyetheretherketone powder to introduce Ag on the surface + Functional groups of , to obtain modified PEEK powder;
[0008] (2) Load Ag + :
[0009] (2.1) Modified PEEK powder is heated in Ag + Soaking in the solution, separating the product, and obtaining a composite product;
[0010] (2.2) After the primary composite product is subjected to heat treatment and ultraviolet light irradiation, step (2.1) is performed again;
[0011] Step (2.2) is performed once or repeatedly for multiple times to obtain antibacterial PEEK powder;
[0012] (3) The antibacterial PEEK powder is sprayed onto the surface of the carbon fiber cloth by electrostatic powder spraying, and then hot pressed after baking.
[0013] In the above process, the mechanism of antibacterial modification of CF / PEEK composite material is as follows: In step (1), by plasma treatment, the free radicals generated by plasma react with polyetheretherketone to form a surface of polyetheretherketone powder that can react with Ag. + Complex functional groups (such as carboxyl groups); in step (2), Ag + Compounded with functional groups, it can bind Ag on the surface of polyetheretherketone powder + In step (3), the antibacterial PEEK powder is coated with powder by electrostatic powder spraying, and then the powder is uniformly adsorbed on the carbon fiber, and then the CF / PEEK composite material with antibacterial properties can be obtained by baking and hot pressing. In addition, compared with the method of sulfonating PEEK with concentrated sulfuric acid in the prior art, the method of the present invention is safer to operate, and the process of introducing functional groups on the surface of PEEK powder by plasma is more controllable.
[0014] The present invention loads Ag + During the process, multiple immersion deposition of Ag was performed + method, and deposited Ag in each immersion + After that, heat treatment and UV irradiation are performed, and then the next immersion deposition of Ag is carried out. + In this way, more antibacterial functional sites can be loaded on the PEEK powder, and the bonding force between the silver layer deposited last and the silver layer deposited last is ensured, which is beneficial to reduce the shedding of silver during the composite process of the antibacterial PEEK powder and the carbon fiber cloth and during the use of the antibacterial CF / PEEK composite material, thereby improving the antibacterial properties of the antibacterial CF / PEEK composite material.
[0015] Preferably, in step (1), during the plasma treatment, the treatment gas used is a mixture of oxygen and nitrogen.
[0016] Plasma treatment of polyetheretherketone powder with a mixture of oxygen and nitrogen can introduce different types of active functional groups on the surface of PEEK, which can be used for Ag + Provide chemical binding sites for Ag +The introduction of oxygen-containing groups can increase the surface energy of PEEK powder, making its surface more hydrophilic, thereby increasing the Ag + The introduction of nitrogen-containing groups can improve the microstructure of the PEEK powder surface, making it more suitable for Ag + Through the above method, the CF / PEEK composite material can be given better antibacterial properties.
[0017] Preferably, in step (2.2), the heat treatment temperature is 60-100° C. and the time is 0.5-1 h.
[0018] Preferably, in step (2.2), the ultraviolet light irradiation time is 20-40 min.
[0019] Preferably, in step (2.1), the soaking temperature is 25-50°C and the soaking time is 10-120 min.
[0020] Preferably, step (2.2) is performed 1-2 times.
[0021] Preferably, in step (2.1), the process of separating the product comprises the following steps: + After taking it out of the solution, wash away the unbound Ag on the surface + , and then dry.
[0022] Preferably, in step (1), the conditions of the plasma treatment are as follows: power is 50-200 W, gas flow rate is 10-100 cm 3 / min, the volume ratio of oxygen to nitrogen is 1:0.5-2, the pressure is 0.1-10 Torr, and the time is 10-60min.
[0023] Preferably, in step (2.1), the Ag + The concentration of the solution is 0.01-0.1 mmol / L.
[0024] Preferably, in step (1), the particle size of the polyetheretherketone powder is 10-90 µm.
[0025] Preferably, in step (1), before plasma treatment, the polyetheretherketone powder is first cleaned with ethanol or deionized water and then dried.
[0026] Preferably, in step (3), before spraying the antibacterial PEEK powder onto the surface of the carbon fiber cloth, the carbon fiber cloth is first baked to remove the epoxy resin layer.
[0027] Preferably, in step (1), after the plasma treatment is completed, the product is washed with deionized water and then vacuum dried at 30-60° C. to obtain modified PEEK powder.
[0028] In a second aspect, the present invention provides an antibacterial CF / PEEK composite material obtained by the preparation method.
[0029] In a third aspect, the present invention provides the use of the antibacterial CF / PEEK composite material in orthopedic internal fixation devices.
[0030] Compared with the prior art, the present invention has the following advantages:
[0031] (1) The present invention firstly treats polyetheretherketone with plasma and then reacts with Ag + Combining them can give CF / PEEK composite materials better antibacterial properties, and the operation is safer and more controllable.
[0032] (2) In the process of plasma treatment of polyetheretherketone powder, the present invention uses a mixed gas of oxygen and nitrogen as the treatment gas, which can promote Ag to a greater extent. + and improve the adhesion of Ag + The distribution uniformity of CF / PEEK composites can be improved, thereby improving the antibacterial properties of CF / PEEK composites.
[0033] (3) The present invention loads Ag + During the process, multiple immersion deposition of Ag was performed + In this way, heat treatment and ultraviolet light irradiation are performed after each immersion deposition, and then the next immersion deposition is performed. This can load more antibacterial functional sites on the surface of PEEK powder and improve the bonding force between the silver layer deposited in the latter time and the silver layer deposited in the previous time, thereby improving the antibacterial properties of CF / PEEK composite materials. DETAILED DESCRIPTION
[0034] The present invention will be further described below in conjunction with the embodiments.
[0035] Overall embodiment
[0036] A method for preparing an antibacterial CF / PEEK composite material comprises the following steps:
[0037] (1) Plasma treatment of polyetheretherketone powder to introduce Ag on the surface + Functional groups of the modified PEEK powder were obtained;
[0038] (2) Load Ag + :
[0039] (2.1) Modified PEEK powder is heated in Ag + Soaking in the solution, separating the product, and obtaining a composite product;
[0040] (2.2) After the primary composite product is subjected to heat treatment and ultraviolet light irradiation, step (2.1) is performed again;
[0041] Step (2.2) is performed once or repeatedly for multiple times to obtain antibacterial PEEK powder;
[0042] (3) The antibacterial PEEK powder is sprayed onto the surface of the carbon fiber cloth by electrostatic powder spraying, and then hot pressed after baking.
[0043] As a specific implementation, in step (1), the particle size of the polyetheretherketone powder is 10-90 µm.
[0044] As a specific implementation, in step (1), before plasma treatment, the polyetheretherketone powder is first cleaned with ethanol or deionized water and then dried.
[0045] As a specific embodiment, in step (1), the conditions of the plasma treatment are as follows: the power is 50-200 W, the treatment gas is a mixture of oxygen and nitrogen in a volume ratio of 1:0.5-2, and the gas flow rate is 10-100 cm 3 / min, pressure 0.1-10 Torr, time 10-60 min.
[0046] As a specific implementation, in step (1), after the plasma treatment is completed, the product is washed with deionized water and then vacuum dried at 30-60° C. to obtain modified PEEK powder.
[0047] As a specific implementation, in step (2), the Ag + The concentration of the solution is 0.01-0.1 mmol / L.
[0048] As a specific embodiment, in step (2.1), the Ag + The concentration of the solution is 0.01-0.1 mmol / L.
[0049] As a specific implementation, in step (2.1), the soaking temperature is 25-50°C and the soaking time is 10-120 min.
[0050] As a specific implementation, in step (2.2), the heat treatment temperature is 60-100°C and the time is 0.5-1 h.
[0051] As a specific implementation, in step (2.2), the ultraviolet light irradiation time is 20-40 min.
[0052] As a specific implementation, in step (3), before spraying the antibacterial PEEK powder onto the surface of the carbon fiber cloth, the carbon fiber cloth is first baked to remove the epoxy resin layer.
[0053] An antibacterial CF / PEEK composite material obtained by adopting the preparation method.
[0054] Application of the antibacterial CF / PEEK composite material in orthopedic internal fixation equipment. Specific embodiments
[0056] The present invention is described below by specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention, and the attached claims and any equivalents thereof are the protection scope of the present invention.
[0057] Unless otherwise defined, all technical terms and scientific terms used in the present invention have the same meanings as those commonly understood by ordinary technicians in the field to which the present disclosure belongs. Unless otherwise specified, the raw materials and equipment used in the present invention are conventional raw materials and equipment in the field and can be obtained from conventional commercial channels; unless otherwise specified, the methods used in the present invention are conventional methods in the field.
[0058] Example 1
[0059] A method for preparing an antibacterial CF / PEEK composite sheet is prepared by the following steps:
[0060] (1) PEEK powder (particle size range: 10-90 µm) was washed with ethanol to remove surface impurities and ensure that the sample surface was clean and uncontaminated. It was then vacuum dried at 50 °C for 3 hours to ensure that there was no moisture on the surface to obtain pretreated PEEK powder.
[0061] (2) Turn on the plasma treatment equipment and check the equipment status to ensure that it is operating normally. Connect the treatment gas (a mixture of oxygen and nitrogen with a volume ratio of 1:0.5) to the equipment. Set the plasma treatment power to 50 W and the gas flow rate to 10 cm 3 / min, treatment time is 60 min, and treatment pressure is 0.1 Torr. The pretreated PEEK powder is placed in the treatment chamber, the plasma treatment equipment is started and the treatment is started. After treatment, it is gently rinsed with deionized water to remove any possible residues, and then vacuum dried at 50°C to obtain modified PEEK powder, which is stored for later use.
[0062] (3) Prepare a 0.01 mmol / L silver nitrate (AgNO3) solution.
[0063] (4) Immerse the modified PEEK powder obtained in step (2) into the silver nitrate solution prepared in step (3) at a mass volume ratio of 1 g:10 mL. Gently stir the solution to ensure that the modified PEEK powder is completely immersed and evenly contacts the solution. React at 50°C for 10 min. Then rinse the reacted powder thoroughly with deionized water to remove unreacted silver ions and excess silver nitrate solution on the surface, and then vacuum dry at 50°C for 2 hours to remove all moisture to obtain a primary composite product.
[0064] (5) The composite product obtained in step (4) was placed in an oven and heated at 60°C for 1 h, and then placed under a UV light source and irradiated for 40 min, and then step (4) was performed again. This step was performed twice in total to obtain antibacterial PEEK powder.
[0065] (6) The carbon fiber cloth was baked at 400°C for 30 min to remove the epoxy resin layer coated on the fiber surface. Then, the antibacterial PEEK powder obtained in step (5) was sprayed and adsorbed onto the surface of the carbon fiber cloth using an electrostatic powder spraying device, and the mass ratio of the antibacterial PEEK powder to the carbon fiber cloth was 2:1. The obtained product was then baked at 300°C for 5 min and air-cooled to obtain a woven CF / PEEK prepreg.
[0066] (7) The woven CF / PEEK prepreg obtained in step (6) was cut into sheets and stacked in a hot pressing mold cavity of the same size. The upper and lower molds were heated to the forming temperature (380°C), and the hot pressing mold containing the woven CF / PEEK prepreg was placed in the upper and lower molds. The temperature was raised from room temperature to the forming temperature (380°C) at a heating rate of 15°C / min without applying pressure; then a pressure of 6 MPa was applied and maintained for 20 min; and then cooled and solidified at a cooling rate of 5°C / min to obtain an antibacterial CF / PEEK composite sheet.
[0067] The antibacterial CF / PEEK composite sheet prepared in this embodiment was tested for antibacterial performance against Staphylococcus aureus, and the test method was based on WS / T650-2019. The measured antibacterial rate was 99.9%.
[0068] Example 2
[0069] A method for preparing an antibacterial CF / PEEK composite sheet is prepared by the following steps:
[0070] (1) PEEK powder (particle size range: 10-90 µm) was washed with ethanol to remove surface impurities and ensure that the sample surface was clean and uncontaminated. It was then vacuum dried at 50 °C for 3 hours to ensure that there was no moisture on the surface to obtain pretreated PEEK powder.
[0071] (2) Turn on the plasma treatment equipment and check the equipment status to ensure normal operation. Connect the treatment gas (a mixture of oxygen and nitrogen with a volume ratio of 1:2) to the equipment. Set the plasma treatment power to 200 W and the gas flow rate to 100 cm 3 / min, treatment time is 60 min, and treatment pressure is 10 Torr. The pretreated PEEK powder is placed in the treatment chamber, the plasma treatment equipment is started and the treatment is started. After treatment, it is gently rinsed with deionized water to remove any possible residues, and then vacuum dried at 50°C to obtain modified PEEK powder, which is stored for later use.
[0072] (3) Prepare a 0.1 mmol / L silver nitrate (AgNO3) solution.
[0073] (4) Immerse the modified PEEK powder obtained in step (2) into the silver nitrate solution prepared in step (3) at a mass volume ratio of 1 g:10 mL. Gently stir the solution to ensure that the modified PEEK powder is completely immersed and evenly contacts the solution. React at 25°C for 120 min. Then rinse the reacted powder thoroughly with deionized water to remove unreacted silver ions and excess silver nitrate solution on the surface, and then vacuum dry at 50°C for 2 hours to remove all moisture to obtain a primary composite product.
[0074] (5) The primary composite product obtained in step (4) is placed in an oven and heated at 100° C. for 0.5 h, and then placed under an ultraviolet light source and irradiated for 20 min, and then step (4) is performed again to obtain antibacterial PEEK powder.
[0075] (6) The carbon fiber cloth was baked at 400°C for 30 min to remove the epoxy resin layer coated on the fiber surface. Then, the antibacterial PEEK powder obtained in step (5) was sprayed and adsorbed onto the surface of the carbon fiber cloth using an electrostatic powder spraying device, and the mass ratio of the antibacterial PEEK powder to the carbon fiber cloth was 2:1. The obtained product was then baked at 300°C for 5 min and air-cooled to obtain a woven CF / PEEK prepreg.
[0076] (7) The woven CF / PEEK prepreg obtained in step (6) was cut into sheets and stacked in a hot pressing mold cavity of the same size. The upper and lower molds were heated to the forming temperature (380°C), and the hot pressing mold containing the woven CF / PEEK prepreg was placed in the upper and lower molds. The temperature was raised from room temperature to the forming temperature (380°C) at a heating rate of 15°C / min without applying pressure; then a pressure of 6 MPa was applied and maintained for 20 min; and then cooled and solidified at a cooling rate of 5°C / min to obtain an antibacterial CF / PEEK composite sheet.
[0077] The antibacterial CF / PEEK composite sheet prepared in this embodiment was tested for its antibacterial performance against Staphylococcus aureus using the same testing method as in Example 1, and the antibacterial rate was measured to be 99.9%.
[0078] Comparative Example 1
[0079] The difference between this comparative example and Example 1 is that: + In the process, after each immersion deposition, the next immersion deposition is performed without heat treatment and ultraviolet irradiation. The specific steps of preparing the antibacterial CF / PEEK composite sheet in this comparative example are as follows:
[0080] (1) PEEK powder (particle size range: 10-90 µm) was washed with ethanol to remove surface impurities and ensure that the sample surface was clean and uncontaminated. It was then vacuum dried at 50 °C for 3 hours to ensure that there was no moisture on the surface to obtain pretreated PEEK powder.
[0081] (2) Turn on the plasma treatment equipment and check the equipment status to ensure that it is operating normally. Connect the treatment gas (a mixture of oxygen and nitrogen with a volume ratio of 1:0.5) to the equipment. Set the plasma treatment power to 50 W and the gas flow rate to 10 cm 3 / min, treatment time is 60 min, and treatment pressure is 0.1 Torr. The pretreated PEEK powder is placed in the treatment chamber, the plasma treatment equipment is started and the treatment is started. After treatment, it is gently rinsed with deionized water to remove any possible residues, and then vacuum dried at 50°C to obtain modified PEEK powder, which is stored for later use.
[0082] (3) Prepare a 0.01 mmol / L silver nitrate (AgNO3) solution.
[0083] (4) Immerse the modified PEEK powder obtained in step (2) into the silver nitrate solution prepared in step (3) at a mass volume ratio of 1 g: 10 mL. Gently stir the solution to ensure that the modified PEEK powder is completely immersed and evenly contacts the solution. React at 50°C for 10 min. Then rinse the reacted powder thoroughly with deionized water to remove unreacted silver ions and excess silver nitrate solution on the surface, and then vacuum dry at 50°C for 2 hours to remove all moisture. This step is performed 3 times to obtain antibacterial PEEK powder.
[0084] (5) The carbon fiber cloth was baked at 400°C for 30 min to remove the epoxy resin layer coated on the fiber surface. Then, the antibacterial PEEK powder obtained in step (4) was sprayed and adsorbed onto the surface of the carbon fiber cloth using an electrostatic powder spraying device, and the mass ratio of the antibacterial PEEK powder to the carbon fiber cloth was 2:1. The obtained product was then baked at 300°C for 5 min and air-cooled to obtain a woven CF / PEEK prepreg.
[0085] (6) The woven CF / PEEK prepreg obtained in step (5) was cut into sheets and stacked in a hot pressing mold cavity of the same size. The upper and lower molds were heated to the forming temperature (380°C), and the hot pressing mold containing the woven CF / PEEK prepreg was placed in the upper and lower molds. The temperature was raised from room temperature to the forming temperature (380°C) at a heating rate of 15°C / min without applying pressure; then a pressure of 6 MPa was applied and maintained for 20 min; and then cooled and solidified at a cooling rate of 5°C / min to obtain an antibacterial CF / PEEK composite sheet.
[0086] The antibacterial CF / PEEK composite sheet prepared in this comparative example was tested for its antibacterial performance against Staphylococcus aureus using the same testing method as in Example 1, and the antibacterial rate was measured to be 92.2%.
[0087] Comparative Example 2
[0088] The difference between this comparative example and Example 1 is that: + In the process, after each immersion deposition, the next immersion deposition is performed without UV irradiation. The specific steps of preparing the antibacterial CF / PEEK composite sheet in this comparative example are as follows:
[0089] (1) PEEK powder (particle size range: 10-90 µm) was washed with ethanol to remove surface impurities and ensure that the sample surface was clean and uncontaminated. It was then vacuum dried at 50 °C for 3 hours to ensure that there was no moisture on the surface to obtain pretreated PEEK powder.
[0090] (2) Turn on the plasma treatment equipment and check the equipment status to ensure that it is operating normally. Connect the treatment gas (a mixture of oxygen and nitrogen with a volume ratio of 1:0.5) to the equipment. Set the plasma treatment power to 50 W and the gas flow rate to 10 cm 3 / min, treatment time is 60 min, and treatment pressure is 0.1 Torr. The pretreated PEEK powder is placed in the treatment chamber, the plasma treatment equipment is started and the treatment is started. After treatment, it is gently rinsed with deionized water to remove any possible residues, and then vacuum dried at 50°C to obtain modified PEEK powder, which is stored for later use.
[0091] (3) Prepare a 0.01 mmol / L silver nitrate (AgNO3) solution.
[0092] (4) Immerse the modified PEEK powder obtained in step (2) into the silver nitrate solution prepared in step (3) at a mass volume ratio of 1 g:10 mL. Gently stir the solution to ensure that the modified PEEK powder is completely immersed and evenly contacts the solution. React at 50°C for 10 min. Then rinse the reacted powder thoroughly with deionized water to remove unreacted silver ions and excess silver nitrate solution on the surface, and then vacuum dry at 50°C for 2 hours to remove all moisture to obtain a primary composite product.
[0093] (5) The composite product obtained in step (4) was placed in an oven, heated at 60°C for 1 h, and step (4) was performed again. This step was performed twice in total to obtain antibacterial PEEK powder.
[0094] (6) The carbon fiber cloth was baked at 400°C for 30 min to remove the epoxy resin layer coated on the fiber surface. Then, the antibacterial PEEK powder obtained in step (5) was sprayed and adsorbed onto the surface of the carbon fiber cloth using an electrostatic powder spraying device, and the mass ratio of the antibacterial PEEK powder to the carbon fiber cloth was 2:1. The obtained product was then baked at 300°C for 5 min and air-cooled to obtain a woven CF / PEEK prepreg.
[0095] (7) The woven CF / PEEK prepreg obtained in step (6) was cut into sheets and stacked in a hot pressing mold cavity of the same size. The upper and lower molds were heated to the forming temperature (380°C), and the hot pressing mold containing the woven CF / PEEK prepreg was placed in the upper and lower molds. The temperature was raised from room temperature to the forming temperature (380°C) at a heating rate of 15°C / min without applying pressure; then a pressure of 6 MPa was applied and maintained for 20 min; and then cooled and solidified at a cooling rate of 5°C / min to obtain an antibacterial CF / PEEK composite sheet.
[0096] The antibacterial CF / PEEK composite sheet prepared in this comparative example was tested for antibacterial performance against Staphylococcus aureus using the same testing method as in Example 1, and the measured antibacterial rate was 93.8%. The antibacterial performance of this comparative example is lower than that of Example 1, but higher than that of Comparative Example 1, indicating that the Ag deposition rate of each immersion is significantly higher than that of the immersion layer. + Heat treatment during the process can improve the antibacterial properties of the CF / PEEK composite sheet, and ultraviolet light irradiation after the heat treatment can further improve the antibacterial properties of the resulting material.
[0097] Comparative Example 3
[0098] The only difference between this comparative example and Example 1 is that oxygen is used as the processing gas during the plasma treatment. The specific steps for preparing the antibacterial CF / PEEK composite sheet in this comparative example are as follows:
[0099] (1) PEEK powder (particle size range: 10-90 µm) was washed with ethanol to remove surface impurities and ensure that the sample surface was clean and uncontaminated. It was then vacuum dried at 50 °C for 3 hours to ensure that there was no moisture on the surface to obtain pretreated PEEK powder.
[0100] (2) Turn on the plasma treatment equipment and check the equipment status to ensure that it is operating normally. Connect the treatment gas (oxygen) to the equipment. Set the plasma treatment power to 50 W and the gas flow rate to 10 cm 3 / min, treatment time is 60 min, and treatment pressure is 0.1 Torr. The pretreated PEEK powder is placed in the treatment chamber, the plasma treatment equipment is started and the treatment is started. After treatment, it is gently rinsed with deionized water to remove any possible residues, and then vacuum dried at 50°C to obtain modified PEEK powder, which is stored for later use.
[0101] (3) Prepare a 0.01 mmol / L silver nitrate (AgNO3) solution.
[0102] (4) Immerse the modified PEEK powder obtained in step (2) into the silver nitrate solution prepared in step (3) at a mass volume ratio of 1 g:10 mL. Gently stir the solution to ensure that the modified PEEK powder is completely immersed and evenly contacts the solution. React at 50°C for 10 min. Then rinse the reacted powder thoroughly with deionized water to remove unreacted silver ions and excess silver nitrate solution on the surface, and then vacuum dry at 50°C for 2 hours to remove all moisture to obtain a primary composite product.
[0103] (5) The composite product obtained in step (4) was placed in an oven and heated at 60°C for 1 h, and then placed under a UV light source and irradiated for 40 min, and then step (4) was performed again. This step was performed twice in total to obtain antibacterial PEEK powder.
[0104] (6) The carbon fiber cloth was baked at 400°C for 30 min to remove the epoxy resin layer coated on the fiber surface. Then, the antibacterial PEEK powder obtained in step (5) was sprayed and adsorbed onto the surface of the carbon fiber cloth using an electrostatic powder spraying device, and the mass ratio of the antibacterial PEEK powder to the carbon fiber cloth was 2:1. The obtained product was then baked at 300°C for 5 min and air-cooled to obtain a woven CF / PEEK prepreg.
[0105] (7) The woven CF / PEEK prepreg obtained in step (6) was cut into sheets and stacked in a hot pressing mold cavity of the same size. The upper and lower molds were heated to the forming temperature (380°C), and the hot pressing mold containing the woven CF / PEEK prepreg was placed in the upper and lower molds. The temperature was raised from room temperature to the forming temperature (380°C) at a heating rate of 15°C / min without applying pressure; then a pressure of 6 MPa was applied and maintained for 20 min; and then cooled and solidified at a cooling rate of 5°C / min to obtain an antibacterial CF / PEEK composite sheet.
[0106] The antibacterial CF / PEEK composite sheet prepared in this comparative example was tested for antibacterial performance against Staphylococcus aureus using the same testing method as in Example 1, and the measured antibacterial rate was 96.0%. The antibacterial performance of this comparative example is lower than that of Example 1, indicating that in the process of plasma treatment of PEEK powder, the use of a mixed gas of oxygen and nitrogen can give the CF / PEEK composite sheet better antibacterial performance than the use of oxygen as the treatment gas.
[0107] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing an antibacterial CF / PEEK composite material, characterized in that: The following steps are involved: (1) Using a mixture of oxygen and nitrogen as a treatment gas, the polyetheretherketone powder is subjected to plasma treatment to introduce functional groups on the surface to obtain modified PEEK powder; the conditions of the plasma treatment are as follows: the power is 50-200 W, the gas flow rate is 10-100 cm 3 / min, the volume ratio of oxygen to nitrogen is 1:0.5-2, the pressure is 0.1-10 Torr, and the time is 10-60 min; (2) Load Ag + : (2.1) Modified PEEK powder is heated in Ag + Soaking in the solution, separating the product, and obtaining a composite product; (2.2) After the primary composite product is subjected to heat treatment and ultraviolet light irradiation, step (2.1) is performed again; Step (2.2) is performed once or repeatedly for multiple times to obtain antibacterial PEEK powder; (3) The antibacterial PEEK powder is sprayed onto the surface of the carbon fiber cloth by electrostatic powder spraying, and then hot pressed after baking.
2. The preparation method according to claim 1, characterized in that In step (2.2), the heat treatment temperature is 60-100°C and the time is 0.5-1 h.
3. The preparation method according to claim 1, characterized in that In step (2.2), the ultraviolet light irradiation time is 20-40 min.
4. The preparation method according to claim 1, characterized in that In step (2.1), the soaking temperature is 25-50°C and the soaking time is 10-120 min.
5. The preparation method according to claim 1, characterized in that In step (2.1), the Ag + The concentration of the solution is 0.01-0.1 mmol / L.
6. The preparation method according to claim 1, characterized in that In step (1), the particle size of the polyetheretherketone powder is 10-90 µm.
7. An antibacterial CF / PEEK composite material, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the antibacterial CF / PEEK composite material as claimed in claim 7 in orthopedic internal fixation devices.
Citation Information
Patent Citations
Biomaterials with antibacterial and osteogenic integration properties, their preparation methods and applications
CN112898619B
Composite bone plate of carbon fiber and polyether-ether-ketone and preparation method thereof
CN106620895A
Preparation method of modified polyether-ether-ketone with antibacterial property on surface
CN117327322A